A Review on Consequences of Alcohol Consumption (International Journal of Food and Nutritional Sciences, 2022)
This message highlights current perspectives on the immunomodulatory effects of acute and chronic alcohol intake by reviewing recent research. Chronic and even acute, moderate alcohol use may enhance the host's susceptibility to bacterial and viral illnesses. Reduced inflammatory response, altered cytokine production, and aberrant reactive oxygen intermediate formation seem to be related to impaired host defense following alcohol consumption. Furthermore, both acute and chronic alcohol consumption impairs cellular immunity, especially antigen-specific immune response. Although ethanol may impact T lymphocyte activity directly, reduced antigen presentation cell function seems to be a major component in the ethanol-induced reduction in cell-mediated immunity. Furthermore, based on the higher immunoglobulin levels observed in chronic alcoholics, a preferential activation of Th2 versus Th1 immune response has been proposed. The functional abnormalities of T and B lymphocytes, natural killer cells, and monocytes/macrophages that result in the altered immune response seen after alcohol use are discussed in the context of the effects of chronic and acute alcohol consumption on host defense and immunity in humans, animal models, and in vitro systems.